Antihelmintic and anticoccidial effects of zingiber officinale roscoe fortified diets fed yankasa rams (2017)
Parasitic burden results in sub-optimal ruminant livestock production. Synthetic coccidiostats and antihelminthes have been reported to induce resistance and leave residues in the carcass of animals with serious health implications. Although ginger rhizome is a potential alternative to coccidiostats and antihelminthes, its use has not been properly documented. In this study, ginger rhizome was processed into powder and added to a concentrate diet at 0g/kg (G1), 5g/kg (G2), 10g/kg (G3), 15g/kg (G4) and 20g/kg (G5). In a completely randomized design, twenty five pubertal Yankasa rams were allotted to the five dietary treatments. The rams were allowed to graze inside infested pastures for 50days to acquire helminthes and coccidia naturally. At day 51, the rams were confine in individual pens and fed experimental diets for 28days. Faecal samples (5g) were collected from rams for Faecal Egg Count Reduction Test (FECRT, %)) and Coccidia Oocyst Reduction Test (CORT, %) on days 0, 7, 14, 21 and 28. Data obtained were subjected to descriptive statistics and ANOVA α0.05. Results obtained showed that on day 28, the FECRT (%) was higher in G2 (100), G3 (100), G4(100) and G5(100) than G1 (7.43) while the CORT (%) was higher in G2 (100), G3 (100), G4 (98.83) and G5 (100) than G1 (22.60). The helminthes ova recovered from faecal examination using floatation techniques were Haemonchus contortus, Trichostrongylus spp, Oesophagostomum spp, Strongyloides,and Moniezia; while Haemonchus contortus, Trichostrongylus spp., Nematodirus spp., Moniezia and Oesophagostomum spp. larvae were identified on faecal culture. The result revealed that crude ginger rhizome is a potential alternative anti-helminth and anti-coccidia for resource poor farmers as it grossly reduced helminth and coccidia load in the rams.